The invasive cytopathologist : ultrasound guided fine-needle aspiration of superficial masses - Bardales, Ricardo H. (Essentials in Cytopathology,, 2014)
The Invasive Cytopathologist: Ultrasound Guided Fine-Needle Aspiration of Superficial Masses provides a comprehensive review of the cytology of superficial neoplastic and non-neoplastic disease processes obtained by percutaneous ultrasound guidance, particularly of thyroid, parathyroid, lymph nodes, salivary glands, breast, and soft tissue with ultrasound image and histopathology correlation. This book emphasizes the basic ultrasound characteristics of thyroid nodules, the cytology of common and uncommon neoplastic and non-neoplastic processes according to the Bethesda System for Reporting Thyroid Cytopathology, and provides a technical guide for how to perform ultrasound-guided FNA of thyroid nodules to obtain adequate material for diagnosis. The volume also briefly reviews the molecular aspects of thyroid neoplasia useful for targeted therapy. The Invasive Cytopathologist: Ultrasound Guided Fine-Needle Aspiration of Superficial Masses is a useful guide for ultrasound evaluation, cytological interpretation and differential diagnostic considerations of superficial masses, and is a valuable source of information for cytopathologists, cytopathology fellows, cytotechnology students and upper level pathology residents. Endocrinologists, thyroidologists, head and neck specialists, and any professional with interest in ultrasound and fine needle aspiration cytology of superfial masses will benefit from this book.